2013
DOI: 10.1017/s0022149x13000229
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cage farming on infection of the corvine fishPlagioscion squamosissimus(Perciformes: Sciaenidae) with metacercariae ofAustrodiplostomum compactum(Digenea: Diplostomidae) from the Chavantes reservoir, São Paulo State, Brazil

Abstract: The development of cage fish farms has been associated with an increase in parasitic diseases. Organic matter resulting from feed waste and faeces attracts animals such as birds and invertebrates that can act as hosts for parasites. The aim of this study was to evaluate the influence of cage farming on Austrodiplostomum compactum metacercariae infections of Plagioscion squamosissimus collected close to a cage farm in the Chavantes reservoir (Paranapanema River). Thirty-seven fish were collected in an area clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Most reports on A. compactum in P. squamosissimus describe high prevalence rates, often over 90% (KOHN et al, 1995;MARTINS et al, 2002;SANTOS et al, 2002;MACHADO et al, 2005;PAES et al, 2010a,b;RAMOS et al, 2014). Thus, in view of the 100% prevalence rate and high average parasite intensity (46.9), represented by up to 206 parasites in a single host, the data obtained here are similar to the findings of other authors (KOHN et al, 1995;SANTOS et al, 2002;MACHADO et al, 2005;PAES et al, 2010a, b), confirming the parasite's preference for croakers, as reported by Yamada et al (2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reports on A. compactum in P. squamosissimus describe high prevalence rates, often over 90% (KOHN et al, 1995;MARTINS et al, 2002;SANTOS et al, 2002;MACHADO et al, 2005;PAES et al, 2010a,b;RAMOS et al, 2014). Thus, in view of the 100% prevalence rate and high average parasite intensity (46.9), represented by up to 206 parasites in a single host, the data obtained here are similar to the findings of other authors (KOHN et al, 1995;SANTOS et al, 2002;MACHADO et al, 2005;PAES et al, 2010a, b), confirming the parasite's preference for croakers, as reported by Yamada et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the first description of A. compactum was made by Kohn et al (1995), and since then, this parasite has been reported in over 30 species, indicating low host specificity (RAMOS et al, 2014). The presence of this parasite in fish eyes can cause total or partial loss of vision, making the fish more vulnerable to predation and facilitating the parasite's transmission to the definitive host (EIRAS, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Cage fish farming can also enhance interactions between parasites and hosts. Ramos et al (2014) identified an increase in infections caused by Austrodiplostomum compactum metacercariae in Curvina P. squamosissimus collected close to a cage fish farm in the Chavantes reservoir in the Paranapanema River (between the states of São Paulo and Paraná, Brazil), compared to individuals from a control site. Accord to authors, the presence of cage farm potentiated the infections of metacercariae in Curvina eyes, probably due to the organic enrichment of the sediment and water.…”
Section: Ecological Interactionsmentioning
confidence: 96%
“…Studies on cage fish farm in freshwater systems have demonstrated changes in wild fish species on reproductive aspects of Pimelodus maculatus (Brandão et al, 2014) and influence parasitological factors in Plagioscion squamosissimus (Ramos et al, 2014). In addition, interference in settlement patterns has also been reported (Agostinho et al, 2007;Mallasen et al, 2012) due to the input of organic matter from cages and the introduction of non-native species (Zanatta et al, 2010), mainly through fish escaping from cultivation (Agostinho et al, 2007).…”
Section: Introductionmentioning
confidence: 99%